Proposal for used electronic products management in Mexicali - Kahhat, Ramzy; Miller, Reed; Ojeda-Benitez, Sara; Cruz-Sotelo, Samantha; Jauregui-Sesma, Jorge; Gusukuma, Marco (My University, 2022)
Mexicali, a Mexican city located near the US-Mexico border, has faced several challenges related to adopting an integrated e-waste management system. Thus, the main objective of this work is to propose a new system to be implemented in phases. The current system is evaluated using several methodological approaches including field studies, surveys, interviews, and quantitative modeling via material flow analysis. We suggest the need to properly integrate both the formal and informal sectors to achieve the optimal system that mitigates environmental impacts while preserving the positive social and economic traits of the current system. Thus, without supplanting the current reuse, refurbishment, repair and maintenance practices, a hybrid system is proposed, based on a centralized facility that primarily handles those parts or materials that create environmental impacts and health hazards if mishandled. Furthermore, a decentralized transition phase toward the new system is recommended.
PUCP
Keywords: Mexicali; Electronic products; Campus Mexicali